Bacterial glycosidases in pathogenesis and glycoengineering. (September 2014) - Sjögren, Jonathan; Collin, Mattias
ABSTRACT : Glycosylation is a common post-translational protein modification and many key proteins of the immune system are glycosylated. As the true experts of our immune system, pathogenic bacteria produce enzymes that can modify the carbohydrates (glycans) of the defense mechanisms in order to favor bacterial survival and persistence. At the intersection between bacterial pathogenesis and glycobiology, there is an increased interest in studying the bacterial enzymes that modify the protein glycosylation of their colonized or infected hosts. This is of great importance in order to fully understand bacterial pathogenesis, but it also presents itself as a valuable source for glycoengineering and glycoanalysis tools. This article highlights the role of bacterial glycosidases during infections, introduces the use of such enzymes as glycoengineering tools and discusses the potential of further studies in this emerging field.